Comorbidities in newly diagnosed multiple sclerosis patients: A population-based register study in Finland - Ahvenjärvi, Henrik; Krüger, Johanna; Viitala, Matias; Jokinen, Elina; Autio, Henri; Portaankorva, Anne M.; Soilu-Hänninen, Merja; Ryytty, Mervi (SAGE Publications, 2026)
Background
Comorbidities are common among people with multiple sclerosis (pwMS) and have been suggested to affect the usage of disease-modifying treatments (DMTs).
Objectives
We investigated the prevalence and types of comorbidities in newly diagnosed pwMS, as well as the associations between comorbidities and the choice and persistence of the initial DMT.
Methods
This retrospective register study used data from the Finnish MS register (85% of national coverage). The inclusion criteria were a diagnosis of relapsing-remitting MS between 2010 and 2022, the first DMT started between 2016 and 2022, and an age of at least 18 years. The exclusion criteria were a diagnosis of secondary progressive MS and initiation of azathioprine or mitoxantrone.
Results
The inclusion criteria were met by 1630 pwMS. At least one comorbidity was present in 50.9% of the pwMS. Respiratory comorbidities were associated with the choice of medium-efficacy DMT over high-efficacy DMT (OR = 0.58, CI = 0.36–0.91). Multicomorbidity was associated with lower persistence on all DMTs. Additionally, lower persistence on medium-efficacy DMTs was associated with autoimmune and psychiatric comorbidities and the injectable administration route.
Conclusions
Comorbidities are prevalent among newly diagnosed pwMS. Clinicians should consider comorbidities carefully, as they are associated with DMT persistence.